Uncertainty Evaluation of GUM Method for theDigital Indicating Ｒail-weighbridges - AN Ai-min (Journal of Harbin University of Science and Technology)
Aiming at the problem of quantitative accuracy for the verification of digital indicating rail-weighbridges，this paper analyzes the applicability of GUM method and MCM method in uncertainty evaluation， analyzes and researches the measurement principle and verification method of digital indicating rail-weighbridges． The measuring mathematical model for indicating rail-weighbridges was established and uncertainty of indicating rail-weighbridges was evaluated by GUM. It provides a technical basis for perfecting the traceability and transfer system of rail-weighbridges value. Ｒesults show that the uncertainty based on GUM method mainly comes from the uncertainty caused by rail-weighbridges indicator and superior measurement standard. Thus the metrological requirements of the digital indicating rail-weighbridges can be met by using the Chinese test vehicle method for rail- weighbridges.